Kewenangan Komisi Pemberantasan Korupsi Melakukan Penyidikan Dan Penuntutan Tindak Pidana Korupsi Dalam Penegakan Hukum - Putri, Risqiana Sunaryo; Sukarna, Kadi; Sudarmanto, Kukuh (Journal Juridisch, 2023)
This research aims to understand the authority of the Corruption Eradication Commission (KPK) in investigating and prosecuting corruption and understand the constraints and solutions of the KPK's authority in investigating and prosecuting corruption crimes in the context of law enforcement. KPK is an independent institution in Indonesia which was formed to fight corruption with the main task of investigating, prosecuting and eradicating criminal acts of corruption. This is regulated in Law Number 30 of 2002 concerning the Corruption Eradication Commission as amended by Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002. With the changes in provisions in the KPK Law, there have been several changes in the authority of the KPK. The type of research used in this research is normative juridical with statutory approach method, collecting and analyzing legal data, laws and regulations, as well as court decisions related to the KPK's authority. The results of the research show that the KPK has broad authority in investigating and prosecuting corruption. The KPK can carry out wiretapping, search and arrest of corruption suspects, and has the authority to submit charges to court. The KPK also has an independent and professional team of investigators and prosecutors. However, there are several limitations in the KPK's authority. Since 2019, the KPK's authority in wiretapping and searching has been limited by the Indonesian Constitutional Court. Apart from that, there is also debate about the independence status of the Corruption Eradication Committee and political interference that can affect the enforcement of corruption laws. In the context of effective law enforcement, it is important for the KPK to continue to strengthen its authority and ensure its independence from political forces. The active role of the community and government support are also needed to support KPK's efforts to eradicate corruption. Penelitian ini bertujuan untuk memahami kewenangan Komisi Pemberantasan Korupsi (KPK) dalam penyidikan dan penuntutan tindak pidana korupsi serta memahami kendala dan solusi kewenangan KPK dalam penyidikan dan penuntutan tindak pidana korupsi dalam rangka penegakan hukum. KPK adalah lembaga independen di Indonesia yang dibentuk untuk memerangi korupsi dengan tugas utama menyelidiki, menuntut, dan memberantas tindak pidana korupsi. Hal ini diatur dalam Undang-Undang Nomor 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi sebagaimana diubah dengan Undang-Undang Nomor 19 Tahun 2019 tentang Perubahan Kedua Atas Undang-Undang Nomor 30 Tahun 2002. Dengan adanya perubahan ketentuan dalam Undang-Undang KPK, mengakibatkan adanya beberapa perubahahan kewenangan KPK. Jenis penelitian yang digunakan dalam penelitiaan ini adalah yuridis normatif dengan metode pendekatan perundang-undangan, mengumpulkan dan menganalisis data hukum, peraturan perundang-undangan, serta putusan pengadilan terkait kewenangan KPK. Hasil penelitian menunjukkan bahwa KPK memiliki kewenangan yang luas dalam penyidikan dan penuntutan tindak pidana korupsi. KPK dapat melakukan penyadapan, penggeledahan, dan penangkapan terhadap tersangka korupsi, serta memiliki wewenang untuk mengajukan dakwaan ke pengadilan. KPK juga memiliki tim penyidik dan tim penuntut yang independen dan profesional. Namun, ada beberapa keterbatasan dalam kewenangan KPK. Sejak tahun 2019, kewenangan KPK dalam penyadapan dan penggeledahan telah dibatasi oleh Mahkamah Konstitusi Indonesia. Selain itu, ada juga perdebatan mengenai status independensi KPK dan intervensi politik yang dapat mempengaruhi penegakan hukum korupsi. Dalam rangka penegakan hukum yang efektif, penting bagi KPK untuk memperkuat kewenangannya dan memastikan independensinya dari kekuatan politik. Peran aktif masyarakat dan dukungan pemerintah juga diperlukan untuk mendukung upaya pemberantasan korupsi yang dilakukan oleh KPK.